Unspecific congenital toxoplasmosis in a two-month-old baby - Wahdini, Sri; Sari, Ika Puspa; Oswari, Hanifah; Kurniawan, Agnes (Acta Biomedica Atenei Parmensis, 2023)
A two-month-old baby boy diagnosed with unspecific congenital toxoplasmosis was referred by a pediatrician to the Clinical Parasitology referral center at the Faculty of Medicine, Universitas Indonesia. Baby was post-hospitalized in the NICU and required ventilation support for one month. Furthermore, there was history of from various medical conditions, such as intracranial bleeding, convulsion, hypertrophic cardiomyopathy, retinopathy, and renal failure. After two month, there was no significant weight gain, anti-Toxoplasma IgM showed positive results, and anti-Toxoplasma IgM and IgG of the mother were also positive. Baby and mother were successfully treated with pyrimethamine, cotrimoxazole, and folinic acid for one month. At 2 years, there signs of normal motoric, eye, and hearing development with underdeveloped kidneys. Therefore, pre-pregnancy counseling and education aimed at preventing toxoplasmosis during pregnancy should be increased and conducted routinely by health workers or trained cadres to reduce the risk of fetal defects.